الكفارات في الفقه الإسلامي كفارة رمضان أنموذجا - شبحة مسعود; د/ بوفاتح الطيب (جامعة عمار ثليجي الاغواط, 2023)
يهخص انذساعح ض ح٘ٝ صُ ٛزٙ ج ذُسجعس ٞٓمٞع ج لٌُحسجش, ق ٤ع ذ ٤ح أٛ ٤ٔس ٞٓمٞػٜح, ٝأ ٞٗجػٜح, ٝ أق حٌ ٛزٙ ج ٧ ٞٗجع, ٝ حٓ ٣طشضد ػ ٤ِٜح ٝؾٞخ ج لٌُحسز ػذ ٜٓح, ٝر يُ ذؼذ ضطرغ ٝجعطوشجء ج ٧د سُ ج ؾُشػ ٤س, ٝأسجء ج لُوٜحء ك ٤ٜح, ٝهذ جضنف ك ٢ ٛزٙ ج ذُسجعس ٝؾٞد ؾ سِٔ ج ٧ق حٌ ج طُٔلن ػ ٤ِٜح ذ ٤ ج لُوٜحء ٝر يُ ُٞسٝد ج قُ٘ٞؿ ج ُٞجمكس ك ٤ٜح, غٓ ضخ ذؼل ج ٫خط ٬كحش ج طُ ٢ أ طٗؿطٜح ج ٧فٞ ٝج وُٞجػذ ج ؼُٔط ذٔز ػ ذ٘ كش ٣ن ج زُٔجٛد, حًٔ ضل ٛزٙ ج ذُسجعس ؾح رٗ ٤ ٜٓ ٤ٔ ك ٢ ج ذُسجعحش ج ؾُشػ ٤س ٝٛ حٔ: ج كُ سٌٔ ضؾش ٣غ ج لٌُحسجش, ٝج ػُ شٔز ج شُٔؾٞز ضؼ ِٜ حٔ ٝضؼ ٤ِ ٜٔح ٝج ٫ٛط حٔ ذٜح, ٝج ػُح ٤ٗس ر شً ؾح دٗ ج ؤُحفذ لٌُِحسجش, ٝر يُ ذر ٤ح ج ؼُٔح ٢ٗ ج رٌُشٟ ج طُ ٢ أؾ ِٜح ؽشػص ج لٌُحسجش, ٝأ ٛزٙ ج لٌُحسجش ؽشػص صٝجؾش ؾٞجذش ٝعطش لٌُِِٔ ٤ غٓ ػذ ئؿلح ,ٍ كٓحع ج طُؾش ٣غ ج ٩ع ٢ٓ ٬ خ ٬ ٛزٙ ج طُؾش ٣ؼحش ج كُ ٤ٌ سٔ, ج طُ ٢ ذكغ ؽشػٜح ٝق ٤ٌ ٝمؼٜح, أع طٌص ػًشج ج ٧كٞجٙ ج طُ ٢ حٓ كطثص ض ح٘ .ْ ٛزج ج ذُ ٣ ج ؼُظ ٤ Study summary This study dealt with the subject of expiations, in terms of clarifying the importance of its subject, its types, and the provisions of these types, and the consequences of expiation or not, after tracking and extrapolating the legal evidence, and the opinions of the jurists regarding it. between the jurists, due to the presence of clear texts in it, with the permeation of some differences produced by the principles and rules adopted by each group of doctrines, and this study did not overlook two important aspects in legal studies, namely: The wisdom behind legislating expiations, and the desired fruit of learning, teaching and caring for them. The second is mentioning the purposes of expiations, by explaining the major meanings for which expiations were legislated, and that these expiations were legalized as marriages, reprisals and concealments for the taxpayers, without neglecting the virtues of Islamic legislation through these wise legislations. Which, with its good law and wise setting, has silenced many mouths that have been denouncing this great religion.